Correlations between bacterial populations and process parameters in four full-scale anaerobic digesters treating sewage sludge - Shin, Seung Gu; Koo, Taewoan; Lee, Joonyeob; Han, Gyuseong; Cho, Kyungjin; Kim, Woong; Hwang, Seokhwan (Elsevier BV, 2016)
Process parameters and bacterial populations were investigated in four full-scale anaerobic digesters treating sewage sludge. Although the four digesters were operated under similar conditions, digesters A and B had higher pH (7.2-7.4) and lipid removal efficiencies (> 50%) than C and D (pH 6.1-6.4; average lipid removal < 16%). Bacterial richness, diversity, and evenness were higher in digesters C and D. Among the top-populated genera, ten (group I) were more abundant in digesters A and/or B; they were putative syntrophic fatty acid or protein/amino acid-utilizers. In contrast, fifteen others (group II) were less abundant in A and/or B and included potentially dormant/dead cells originated from activated sludge. Despite the overall richness trend, the presence of the 25 genera in groups I/II was greater in digesters A and B (24) than in C and D (17); this observation suggests that group I bacteria might be essential in AD of sewage sludge. (C) 2016 Elsevier Ltd. All rights reserved.